O gato preto de poe: Uma nova visão para um clássico - De Campos, Laís Marin [UNESP] (My University, 2015)
Starting from Tzvetan Todorov's and Remo Ceserani's theory of the Fantastic Literature, this article intente to analyse Poe's The Black Cat, from this theoretical perspective, proposing two new readings for the shor story above.
Poe's The Black Cat: A new vision for a classic